Social Innovations in Islamic Finance: Mobilizing Capital for Maximum Impact on Poverty - Fahad Abdulaziz Ali Almohaimeed (Pakistan Journal of Islamic Research)
In 2002, the United Nations set the targets for its millennium development goals (MDG). This is required more capital for the achievement of these goals, i.e., eradication of poverty, decreasing the degree of hunger, improvement in the state of health, upgradation of the environment and the promotion of sustainable development. However, after putting a lot of efforts it was realized that still there is a need of more capital for achieving these targets. There is still a lot of gap in between the required and available funds from public sources as well as from philanthropy organizations. Therefore, after 16 years it is realized that top priority should be given to the innovative finance. According to Richard Wilcox, a special adviser to the U.N. World Food Program that innovative finance is a huge enterprise. Therefore in 2006, UN  introduced the concept of socially responsible investment (SRI) and the principles for responsible investment (PRI) to promote awareness of environmental, social and governance (ESG) issues.